Helicobacter pylori: From Bench to Bedside. (1st October 1997) - Chiba, N; Matisko, A; Sinclair, P; Thomson, ABR
Abstract : With the exponential increase in research in the field of Helicobacter pylori a paradigm shift has occurred. It is now recognized that H pylori is a chronic infection of the stomach causing inflammation. Some patients remain asymptomatic, while others may develop dyspepsia, duodenal or gastric ulcer, gastric cancer or a mucosa-associated lymphoid tissue lymphoma. However, the role of H pylori in contributing to nonulcer dyspepsia or nonsteroidal anti-inflammatory drug gastropathy remains controversial. An effective vaccine against H pylori is years away. Major interest has focused on the questions "who should be investigated and therefore treated" and "what is the latest gold standard for eradication of H pylori "? In Europe, guidelines have been developed to help the practitioner answer these important questions. Canadian guidelines will soon be available. For persons with known peptic ulcer disease there should be unequivocal acceptance that the good clinical practice of eradicating H pylori will result in substantial savings in health care expenses. The original 'classical triple therapy' (bismuth, metronidazole and tetracycline [BMT]) has now been surpassed by the combination of a proton pump inhibitor (PPI) plus two antibiotics (metronidazole plus clarithromycin; amoxicillin plus clarithromycin; or amoxicillin plus metronidazole), each given twice a day for one week. In Canada, the regimen of omeprazole plus one antibiotic (amoxicillin or clarithromycin) was approved recently but gives an eradication rate that is lower than the current target of 90%. According to the European (Mäastricht) recommendations, if a single treatment attempt with PPI plus two antibiotics fails, PPI plus BMT is recommended.